In vitro activity of macrolides against Streptococcus pneumoniae and Streptococcus pyogenes in the Russian Federation: “Status praesens” - Kozlov R.S.; Ivanchik N.V.; Mikotina A.V.; Dekhnich A.V. (Клиническая микробиология и антимикробная химиотерапия)
Objective.